Escola Cabana na Belém (PA) do partido dos trabalhadores: novos significados e sentidos para educação democrática e popular - Santos, Sandra Costa dos (2017)
This research work has as its central theme the Cabana School, a model of democratic and participatory education that took place in Belém do Pará between 1997 and 2004. During this period, in the city of Belém, a new management model was implemented by the Workers' Party. Endowed with a feeling of revitalization of the historical struggles of the Paraense people, the government of the mayor Edmilson Rodrigues rescued the memory of Cabanagem, popular movement of century XIX. From this model, citizenship and democracy themes were resignified as struggling for better life conditions for paraense people. In the light of the reforms oriented by the growth of neoliberal policies at the national level, PT administration implemented a conception of democratic education focused on the needs of local workers and organized through instruments of popular participation. The central point was to analyze the educational proposal as an alternative response to the hegemonic movement intended by neoliberalism in education. For that, the participatory mechanisms elaborated by the Cabana School project were investigated. The research used was based on interview; bibliographical surveys related to the issue of democratic education; documentary sources entitled Cadernos Cabanos produced to systematize the changes in the municipal education; documents about the management of the Workers' Party in Belém and primary sources on their education proposals as a political party program. As a result, it was verified that the Cabana Education defined the school as a space for discussion of the daily problems and place of construction of a thinking human being based on its own reality. From the confrontation of authoritarian and culturally instituted practices, this educational public policy registered its mark of inclusion and social quality as a path to popular democracy in Belém.